COMPARISON BETWEEN SPINAL ANESTHESIA AND GENERAL ANESTHESIA FOR THE CAESAREAN SECTION: A PROSPECTIVE STUDY - HATAM FAAWY GHADHBAN; NASER MAHDI NASER (Scholar Express Journals, 2022)
The objective of the present study was to compare spinal and general anesthesia with respect to its neonatal outcomes in pregnant women undergoing elective cesarean section [CS]. The present study was a hospitalbased prospective study conducted in Alhindia hospital, Iraq, between January 2020 to August 2020. The pregnant women [n=40] were operated on with two different types of anesthesia methods, viz. general anesthesia operated group [GAOG] and spinal anesthesia operated group [SAOG]. Mother health and neonatal outcome were recorded in both groups. Preoperative and post-operative blood was collected from individuals [mother]. The separated serum was analyzed for various parameters such as hemoglobin [Hb], hematocrit, platelet count, red blood count [RBCs], and total white blood count [TWBCs]. The body mass index was nonsignificantly different in GAOG and SAOG. In the GAOG group, postoperative hemoglobin content, percent hematocrit, haemogram were significantly decreased as compared to their preoperative parameters. The SAOG also showed similar findings. In the postoperative stage, SAOG showed a significantly decrease in the hemoglobin content [p = 0.004], hematocrit content [p = 0.003], platelet count [p = 0.004], and red blood cells value [p = 0.004] as compared to GAOG. In the postoperative stage, SAOG showed a nonsignificant increase in the systolic blood pressure [SBP] and decreases in the diastolic blood pressure [DBP] compared to GAOG. The newborn baby weight was found to be high in spinal anesthesia operated groups compared to GAOG. Apgar scores were higher in the SAOG individuals at 1st min and after a 5th min compared to GAOG. We can conclude that spinal anesthesia was better for the mother's health and higher Apgar score, which is a major evaluation of neonatal outcome
Keywords: Anesthesia; Apgar score; Hemoglobin; Blood pressure